Association of Post-Partum Depression (PPD) with Mother`s Working Status – A Cross-Sectional Study - Malik, Ishel Farid; Tabassum, Ahmed Shoaib; Ayub, Burhan; Ishaq, Hammad; Zaidi, Danish Ali; Zia, Maria (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the association of postpartum depression with mother`s working status in women presenting to tertiary care hospital Study Design: Cross-sectional comparative study. Place and Duration of Study: Department of Psychiatry, Armed Forces Institute of Mental Health, Rawalpindi Pakistan, from Sep 2024 to Feb 2025. Methodology: Three hundred and twenty women during first 6 month of postpartum period were included. Two strata of working women and housewives were made using stratified random sampling. The Edinburgh Postnatal Depression Scale (EPDS) form filled by the participant during an interview by a doctor. Statistical significance checked using Chi square test and non-parametric tests. Cramer’s V was used to check strength of association between mother’s working status and EPDS score. Results: Comparison of EPDS scores between the two groups revealed a significant difference with median [IQR] score of 9.00 [8.10] points and 8.00 [7.01] points in working and non-working women respectively (p=0.046). PPD diagnosed on EPDS score showed 40(25.0%) working women was suffering from depression as compared to 29(18.1%) non-working mothers. The risk of depression among the non-working was found to be less as compared to the working women (p=0.002, Cramer’s V=0.225). Moreover, overall mothers from low socio-economic status found to be suffering from depression as compared to middle or upper socio-economic status mothers. Conclusion: Females with employment status had slightly higher risk of suffering from symptomatic moderate-severe PPD when compared to non-working mothers.